Analysis of anticancer compound, indole-3-carbinol, in broccoli using a new ultrasound-assisted dispersive-filter extraction method based on poly(deep eutectic solvent)-graphene oxide nanocomposite - Yanan Yuan; Huanhuan Chen; Yehong Han; Fengxia Qiao; Hongyuan Yan (Elsevier, 2022)
Indole-3-carbinol (I3C), an important anticancer compound found in broccoli, has attracted considerable attention. The rapid extraction and accurate analysis of I3C in the pharmaceutical industry in broccoli is challenging as I3C is unstable at low pH and high temperature. In this study, a rapid, accurate, and low-cost ultrasound-assisted dispersive-filter extraction (UADFE) technique based on poly(deep eutectic solvent)-graphene oxide (PDES-GO) adsorbent was developed for the isolation and analysis of I3C in broccoli for the first time. PDES-GO with multiple adsorption interactions and a fast mass transfer rate was synthesized to accelerate adsorption and desorption. UADFE was developed by combining dispersive solid-phase extraction (DSPE) and filter solid-phase extraction (FSPE) to realize rapid extraction and separation. Based on the above two strategies, the proposed PDES-GO-UADFE method coupled with high-performance liquid chromatography (HPLC) allowed the rapid (15-16 min), accurate (84.3%-96.4%), and low-cost (adsorbent: 3.00 mg) analysis of I3C in broccoli and was superior to solid-phase extraction, DSPE, and FSPE methods. The proposed method showed remarkable linearity (r=0.9998; range: 0.0840-48.0 μg/g), low limit of quantification (0.0840 μg/g), and high precision (relative standard deviation ≤5.6%). Therefore, the PDES-GO-UADFE-HPLC method shows significant potential in the field of pharmaceutical analysis for the separation and analysis of anti-cancer compounds in complex plant samples.